Lowered oesophageal sensory thresholds in patients with symptomatic but not excess gastro-oesophageal reflux: evidence for a spectrum of visceral sensitivity in GORD. (July 1995) - Trimble, K C; Pryde, A; Heading, R C
Abstract : Some patients undergoing ambulatory oesophageal pH monitoring to investigate symptoms suggestive of gastro-oesophageal reflux disease (GORD) are found to have oesophageal acid exposure within the physiological range but show a close correlation between their symptoms and individual reflux episodes. It is suggested that these patients might exhibit enhanced oesophageal sensation, akin to the heightened perception of both physiological and provocative stimuli in the gut that has been described in patients with functional gastrointestinal disorders. This study tested the hypothesis by measuring the sensory thresholds for oesophageal balloon distension and discomfort in 20 patients with symptoms of GORD, in whom ambulatory pH monitoring had shown normal acid exposure times, but in whom the symptom index for reflux events was 50% or greater, and compared these with 15 healthy volunteer controls, and with control groups with confirmed excess reflux. The study group showed lower thresholds both for initial perception of oesophageal distension, and for discomfort, compared with healthy controls (median ml (range)); 7.5 (2-19) v 12 (6-30) (p = 0.002) and 10 (5-20) v 16 (8-30) (p < 0.0001), respectively. Sensory thresholds in the study group were also significantly lower than in patients with excess reflux, and than patients with Barrett's oesophagus, who also exhibited significantly higher sensory thresholds than healthy controls. No differences in sensory thresholds for somatic nerve stimulation were found between the study group and health controls. The results show a spectrum of visceral sensitivity in GORD, with enhanced oesophageal sensation in patients with symptomatic but not excess gastro-oesophageal reflux, suggesting that their symptoms result from a heightened perception of normal reflux events.